(untitled) (Sciences & Technologie. D, Sciences de la terre, 2007)
The objective of this paper is to show an experimental work elucidating the effect of rock sample sizes on porosity. Otherwise, this testing reveals two domains : - The microscopic effects where a great variations in porosity should be observed. The homogeneous porous medium where the effect of adding or subtracting one or several pores, has no significant influence on the porosity